Analisa Uji Kekerasan Akibat Perlakuan Panas Dengan Media Pendingin Dexlite dan Air Pada Baja VCN-150 dan Baja S45C Menggunakan Metode Vickers - Junaidi Junaidi; Ade Irwan (Universitas Harapan Medan, 2020)
Solar Dexlite for diesel-engined vehicles is able to protect the vehicle's engine properly. Dexlite also has Ecosave Technology which is able to protect the engine from rust so that the engine is better protected and becomes durable and long lasting. VCN 150 steel which is equivalent to AISI AISI 4340 is a type of steel material that is widely used for shafts in conveyor motor rolls. This steel is included in the machinery steel group which is also an alloy steel of Nickel, Chrom and Molybdenum with medium carbon content. This material has good toughness and ductility and has the ability to be hardened so that it is suitable for its designation under the desired operational conditions. However, to increase wear resistance, one way to do this is to increase the hardness of VCN 150. There is a correlation that increasing hardness will increase the wear resistance of a material. One of the efforts made is to carry out a hardening heat treatment process to obtain a martensite structure. The results of the hardness test on S45C carbon steel, the sample raw material is 213 HV, at a cooling rate of quenching is 674 HV, normalizing is 208 HV and annealing is 150 HV. The hardness of steel using the quenching process is higher compared to other cooling rates. Heat treatment of steel samples at a temperature of 850 oC for 30 minutes with different cooling rates gives the effect of changing the microstructure of the steel. The results of microstructure observations before being given heat treatment produced ferrite and pearlite grains and after being subjected to heat treatment with the quenching process produced martensite and cementite grains.